The Determination Of Optimal Inventory Using Markov Chain - Novie Novie; Haryadi Sarjono (Universitas Airlangga, 2013)
The complication of inventory is a crucial problem for the company because inventory is one of the valuable assets for the company. The existence of inventory control is needed so the inventory levels that exist within the company is not in very large (optimal) therefore the costs incurred by the company can be suppressed as minimum as possible. PT NM is a company engaged in spare parts, especially branded cars in West Jakarta. The level of inventories of goods owned by these companies is high because The company did not want to experience stock out of stock but on one side the stock is large enough so the costs incurred by companies such as storage costs of goods becomes even greater. In order to control inventory levels, this study uses a Markov Chain method that can identify optimal inventory level and the expectation of profits earned per month by making estimates of the future demand a previous demand. From the research results shows expectation of profit of each state starting from state 2 to state 10 is Rp 13.146,98921; Rp 12.246,94064; Rp 11.346,61466; Rp 10.444,64569; Rp 9.534,074035; Rp 8.584,408534; Rp 7.484,413248; Rp 5.913,288143; Rp 3.211,609986,-. While the profit expectations that earned by the company per month is Rp 694.233,333, and the optimal inventory level is 50.